Brockphasma spinifemoralis gen. et spec. nov.: a new phasmid genus and new species of Neohiraseini (Phasmida: Necrosciinae) from Vietnam - Ho, George Wai-Chun; Liu, Xing-Yue; Bresseel, Joachim; Constant, Jerome (Zootaxa, 2014)
A new genus of stick insects, Brockphasma Ho gen. nov., with the type-species, Brockphasma spinifemoralis Ho, Liu, Bresseel & Constant spec. nov., is described and illustrated from Vietnam. Both sexes, the egg and the first instar nymph are described and figured. Data on the habitat and natural foodplants are provided. Brockphasma Ho gen. nov. is differentiated from other genera in Neohiraseini by spinose occiput, anterior region of mesonotum with a spinose hump and spinose anterodorsal and posterodorsal carinae of femora. A key to the genera of Neohiraseini from Vietnam is given.